Validity and Reliability of the Short Physical Performance Battery Tool in Institutionalized Spanish Older Adults - Mirian Santamaría-Peláez; Jerónimo J. González-Bernal; Álvaro Da Silva-González; Elena Medina-Pascual; Ana Gentil-Gutiérrez; Jessica Fernández-Solana; Juan Mielgo-Ayuso; Josefa González-Santos (MDPI AG, 2023)
Background: In order to be used safely, accurately and reliably, measuring instruments in the health field must first be validated, for which the study of their psychometric properties is necessary. The Short Physical Performance Battery (SPPB) tool is a widely used clinical assessment test that has been approved for usage across several nations, languages and demographics. Finding SPPB's psychometric properties for a sample of institutionalized older individuals is the aim of this research. Methods: This is a multicenter, retrospective and observational study of the psychometric properties of the Short Physical Performance Battery tool with a convenience sample of 194 institutionalized older adults. Reliability (internal consistency) and validity (construct validity and convergent validity) tests were performed. Results: The results show a very good internal consistency, construct validity and convergent validity. In addition, the factorial structure of the SPPB is provided, which reflects that it is a unidimensional scale. Conclusions: In conclusion, the Short Physical Performance Battery is a valid and reliable tool for use with institutionalized older adults. Its use is recommended as part of the Comprehensive Geriatric Assessment for the evaluation of the physical or functional sphere. This study was not registered.